2014
DOI: 10.1007/s13277-014-2079-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of microRNA-218 and its potential functions by targeting CIP2A and BMI1 genes in melanoma

Abstract: Melanoma is the most aggressive skin cancer, and it is typically resistant or rapidly develops resistance to a variety of chemotherapeutic agents. microRNAs (miRNAs) play a part in the occurrence and development of malignant melanoma. In this study, we analyzed the miR-218 expression level in melanoma patients and cell lines and observed alterations in proliferation, cell cycle, migration, and invasion by increasing miR-218 expression in melanoma cell lines. We also performed bioinformatic analyses using Targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In addition, we confirmed that miR-218, a tumor suppressor in many types of cancers (16)(17)(18), suppressed the expression of MEF2D mRNA by targeting its 3'UTR. In fact, miRNAs have been verified as major regulators of MEF2D expression.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, we confirmed that miR-218, a tumor suppressor in many types of cancers (16)(17)(18), suppressed the expression of MEF2D mRNA by targeting its 3'UTR. In fact, miRNAs have been verified as major regulators of MEF2D expression.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, miR-128 acts as a tumor suppressor by directly targeting Bmi1 and CYP2C9 in prostate cancer and hepatocellular carcinoma, respectively (35,36). Bmi1 can be targeted by miR-203, miR-218 and miR-135a in different malignancies (37)(38)(39). Although abundant transcriptional targets are predicted, most of these have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al have reported that miR-218 is downregulated in melanoma cells. miR-218 regulates the proliferation, migration, and invasion of melanoma cell lines A375 and SK-MEL-2 by targeting CIP2A and BMI1, indicating the pivotal role played by miR-218 in melanoma development (Wei et al, 2014). A previous study conducted by Nishikawa et al (2014) revealed a significant inhibition of cancer cell migration and invasion upon restoration of miR-218 in prostate cancer cell lines (PC3 and DU145).…”
Section: Discussionmentioning
confidence: 91%